The Relationship Between Hip Range of Motion and Pitching Kinematics Related to Increased Elbow Valgus Loads in Collegiate Baseball Pitchers: A Pilot Study - Giorgio Zeppieri Jr; Michelle L Bruner; Jon P Michelini; Kevin W Farmer (North American Sports Medicine Institute, 2021)
# Background Hip range of motion (ROM) during baseball pitching is associated with trunk rotation and shoulder kinematics, which has shown to influence medial elbow valgus loading and pitching performance. The purpose of this study was to measure the relationship between hip rotational ROM and kinematic variables that influence elbow valgus loads in Division 1 collegiate pitchers. # Study Design Descriptive laboratory study. # Methods Three-dimensional pitching motion (Motion Analysis Corp, Santa Rosa, California) analyses were captured for seven Division 1 baseball pitchers. Six kinematic measurements related to medial elbow valgus loading were calculated while the pitchers threw fastballs. Inclinometer measurements were used to measure hip internal (IR), external (ER) ROM, and total rotational arc at the hip (IR + ER ROM). Correlations were used to evaluate the association between hip IR, ER, and total rotational arc ROM (TRARC) and six kinematic variables. # Results Trunk angular velocity was correlated to trail hip ER and TRARC (p <0.01). Lead hip total arc ROM was associated with maximum shoulder ER (p < 0.01). Lead hip IR was correlated to elbow flexion angle at ball release (p < 0.01). # Conclusion Hip ROM during pitching is associated with trunk angular velocity, maximum shoulder ER and elbow flexion angle at ball release. Alterations in hip TRARC appears to influence trunk rotation velocity leading to dependence on increased shoulder ROM and decreased elbow flexion angle at ball release which is associated with diminished pitching performance and excessive medial elbow valgus loads. # Level of Evidence level 3